Experimental validation of feedback approaches for in-cylinder pressure balancing in SI engines. (2nd April 2010) - Li, Po; Shen, Tielong; Kako, Junichi; Liu, Dichen
This paper, the in-cylinder pressure at top dead centre (TDC) is adopted for evaluating the cycle-to-cycle variability and its four-cycle moving average value is taken as the index for balancing. The control schemes including PI, MVC and MPC are tested under different fuel injection strategies, one is with fixed fuel supply and the other is under A/F balancing. In fact, the MVC and MPC methods are developed from a simple statistical ARMA model. In order to avoid the effect of parameters setting improperly, an adaptive method is employed in MPC controller. Finally, all the controllers are validated in a car-used six-cylinder SI engine.